Analisis Efektivitas Rekam Medis Elektronik Berdasarkan Mutu Rekam Medis di Rawat Inap Rumah Sakit Patria IKKT - Hartati, Nala Dwi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the effectiveness of electronic medical records (EMR) based on the quality of medical records in inpatient services at Patria IKKT Hospital. The aim of this study is to evaluate the completeness of data entry, accuracy, timeliness, and compliance in the verification process by the responsible doctor (DPJP). The research method used is retrospective analysis with a cross-sectional approach, conducted in January 2025. The study involves a total sample of inpatient patient medical records recorded in the EMR system. The results indicate that although the EMR has been implemented, several issues related to data completeness and accuracy, as well as the timeliness of verification by DPJP, were identified. Additionally, compliance with verification procedures was found to vary among healthcare providers. This evaluation provides an overview of the effectiveness of EMR usage in supporting service quality at Patria IKKT Hospital, with recommendations to enhance training and standard operating procedures (SOP) related to data entry and verification. Implementing a more consistent EMR usage compliance program could help improve the quality of medical records and inpatient service quality at this hospital.